2022
DOI: 10.3390/su14042216
|View full text |Cite
|
Sign up to set email alerts
|

Predicting User Behaviour Based on the Level of Interactivity Implemented in Blockchain Technologies in Websites and Used Devices

Abstract: Today’s business development processes force companies to find ways to increase the level of interactivity of their products with consumers. One of the ways that companies communicate interactively with users is communication via websites; another way is using a channel that makes the customer more loyal to the company. The aim of this paper is to point out the differences between the effects that interactive and non-interactive blockchain technologies have on users and their behavior, as well as to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…Perceived interactivity and perceived quality are two key determinants of technology adoption and use behavior in the TAM [6,38,39,83]. According to previous research, perceived interactivity plays a vital role in shaping individuals' attitudes and intentions toward technology use [84]. Specifically, studies have found that higher levels of perceived interactivity are associated with a more positive attitude toward technology and a greater intention to use it [28,38,39,[85][86][87].…”
Section: Perceived Conference Interactivity Quality and Behavioral In...mentioning
confidence: 99%
“…Perceived interactivity and perceived quality are two key determinants of technology adoption and use behavior in the TAM [6,38,39,83]. According to previous research, perceived interactivity plays a vital role in shaping individuals' attitudes and intentions toward technology use [84]. Specifically, studies have found that higher levels of perceived interactivity are associated with a more positive attitude toward technology and a greater intention to use it [28,38,39,[85][86][87].…”
Section: Perceived Conference Interactivity Quality and Behavioral In...mentioning
confidence: 99%